Gregory of Nyssa ancient and (post)modern - Ludlow, Morwenna (Oxford New York University Press, 2007)
The fourth-century Christian thinker, Gregory of Nyssa, has been the subject of a huge variety of interpretations over the past fifty years, from historians, theologians, philosophers, and others. In this highly original study, Morwenna Ludlow analyses these recent readings of Gregory of Nyssa and asks: What do they reveal about modern and postmodern interpretations of the Christian past? What do they say about the nature of Gregory's writing? Working thematically through studies ofrecent Trinitarian theology, Christology, spirituality, feminism, and postmodern hermeneutics, Ludlow develops an
Contents; Introduction: The Elusive Gregory; PART I. THE DOCTRINE OF THE TRINITY; PART II. GOD BECAME HUMAN FOR OUR SALVATION; PART III. SEX, GENDER, AND EMBODIMENT; PART IV. THEOLOGY; Select Bibliography; Index
Includes bibliographical references (p. [293]-305) and index
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Gregory -- of Nyssa, Saint -- ca. 335-ca. 394